Juvenile Delinquency in Europe and Beyond Results of the Second International Self-Report Delinquency Study - Junger-Tas, Josine; Marshall, Ineke Haen.; Enzmann, Dirk.; Killias, Martin; Steketee, Majone; Gruszczynska, Beata; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Juvenile Delinquency in Europe and Beyond: Results of the Second International Self-Report Delinquency Study presents the status of juvenile crime and delinquency and its backgrounds in many of the European Union member states as well as in the United States, Canada, Venezuela and Surinam. The book includes information on key issues in juvenile delinquency such as victimization of young people, alcohol and drug use and its relation to juvenile crime, involvement in youth gangs, immigration, family and school and neighborhood situations. It provides insight into different views on what can be considered juvenile crime; what acts are subsumed in its definition and when we can speak about structural delinquent behavior. These insights are based on self-reported information systematically and simultaneously collected from about 70,000 12-15 year old youths in 28 countries. Until recently, the self-report methodology has not been applied on such a large scale in an international context. The results of this survey provide new and unexpected data about those young people who structurally commit criminal acts, as well as on the frequency of the behavior and the conditions that have an impact on offending. The wealth of descriptions and insights in delinquency of all these countries will be of great interest to scholars, students and practitioners because of the special character of the publication; it is a book of reference to everyone interested in the backgrounds of juvenile delinquency.
Western Europe -- History and Design of the ISRD Studies -- The Netherlands -- Belgium -- Germany -- France -- Switzerland -- Austria -- Anglo-Saxon countries -- Ireland -- Canada -- USA -- Northern Europe -- Finland -- Sweden -- Denmark -- Mediterranean countries -- Portugal -- Spain -- Italy -- Cyprus -- Eastern and Central European countries -- Estonia -- Lithuania -- Poland -- Czech Republic -- Hungary -- Slovenia -- Bosnia and Herzegovina -- Russia -- Armenia -- Latin-American countries -- Venezuela -- Surinam -- The Netherlands Antilles and Aruba -- Synthesis and Outlook.
Keywords: SOCIAL SCIENCES; CRIMINOLOGY; DEMOGRAPHY; SOCIAL SCIENCES; CRIMINOLOGY & CRIMINAL JUSTICE; DEMOGRAPHY